Nitric oxide and prostaglandin metabolites profiling in buffaloes with impending postpartum reproductive disorders - PATRA, MANAS KUMAR; KUMAR, HARENDRA; NANDI, SUKDEB (The Indian Journal of Animal Sciences, 2015)
The study was conducted to correlate the periparturient immune status in terms of plasma nitric oxide (NO) and prostaglandin F2α metabolites (PGFM) profile with impending postpartum reproductive disorders in buffaloes. Pregnant buffaloes (40) were observed for occurrence of postpartum reproductive disorders (PRD), i.e. metritis, endometritis and delayed uterine involution during 1 week prepartum to 4 weeks postpartum period. A representative number (6) of buffaloes that did not develop any PRD were included in Gr. 1 (healthy); and the animals with PRD were assigned into Gr. 2 (8). The blood samples were collected at weekly interval from 1 week prepartum to 4 weeks postpartum period. Plasma NO and PGFM were estimated. A significantly higher NO concentration was found at calving (49.00±7.06 vs. 34.44±3.70 μM) and second week (43.60±5.57 vs 24.25±2.34 μM) postpartum in buffaloes affected with PRD as compared to healthy buffaloes. The PGFM level was also higher in buffaloes that developed PRD throughout the periparturient period. However, the concentration of PGFM was significantly higher, particularly at calving (2.51±0.43 vs 1.267±0.30 ng/ml) and second week (1.058±0.22 vs 0.431±0.08 ng/ml) postpartum. Hence, monitoring of plasma nitric oxide and PGFM level would be effective to predict certain reproductive disorders at calving or immediately after parturition in buffaloes.